The Role of Islamic Finance in Advancing Green Economic Development in Indonesia - Taufiq, Awalludin (ITB AAS INDONESIA Surakarta, 2025)
This study examines the role of Islamic finance, specifically green sukuk, in promoting green economic development in Indonesia. As global attention shifts towards sustainable finance, Islamic financial instruments have shown potential for supporting environmentally friendly projects while adhering to Sharia principles. By analyzing Indonesia’s green sukuk issuances, this study explores how Islamic finance mechanisms can address climate change challenges and contribute to sustainable development goals. Primary data were collected through interviews with stakeholders, including government officials, finance professionals, and environmental experts. Findings reveal that green sukuk not only attract a diverse investor base, including those interested in ethical investment, but also significantly support projects in renewable energy and sustainable infrastructure. Despite these achievements, the study identifies regulatory hurdles and the need for standardized environmental impact assessments as challenges to expanding Islamic green finance. The study concludes by recommending increased regulatory support, public awareness campaigns, and collaboration among stakeholders to maximize the potential of Islamic finance in advancing Indonesia’s sustainable development. These insights contribute to a broader understanding of the role Islamic finance can play in achieving green economic growth.